Interactions between Dislocations and Penta-Twins in Metallic Nanocrystals - Yingbin Chen (MDPI AG, 2021)
Dislocation interactions with twin boundary (TB) have been well-established in nanotwinned metals. Penta-twins, as an extreme of crystal twinning, are tacitly assumed to be more effective at blocking dislocation motions than conventional single or coplanar nanotwins. However, the mechanism underlying the interactions between dislocations and penta-twins remains largely unclear. Here, by combining in situ transmission electron microscope (TEM) nanomechanical testing and atomistic simulations, we rationalize the fundamental interactions between dislocations and penta-twins in Au nanocrystals. Our results reveal that the interactions between dislocations and penta-twins show some similar behaviors to the ones in the cases of coplanar nanotwins, including dislocation impedance at TBs, cross-slip into the twinning plane and transmission across the TB. In addition, penta-twins also exhibit some unique behaviors during dislocation interactions, including multiple cross-slip, dislocation-induced core dissociation and climb-induced annihilation/absorption at the penta-twin core. These findings enhance our mechanistic understanding of dislocation behaviors in penta-twins, shedding light on the accessible design of high-performance nanomaterials with multi-twinned nanostructures.